ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA HOTEL BERBINTANG 4 DI KOTA BATAM - Nurlaila Nurlaila; Adi Neka Fatyandri (Journal of Accounting and Management Innovation, 2018)
The focus of this study is to analyzethe and knowing leadership, work condition, compensation,   conflict of work life  affecting employees performance in four star hotels in the city of Batam. The importance of a 4-star hotel for attention to the factors that affect the employee performance that may be good or bad for the hotel. sample were taken from 200 employees from pacific palace hotel, Allium Panorama hotel, Planet holiday hotel, and Novotel hotel is the spread in the city of Batam. The research data that has been collected and analyzed using the program statistical package for social sciences (IBM-SPSS) version 21. Results from this study showed a significant effect of independent on the dependent variable. First, leadership has a significant effect on job performance. Second, the work condition has a significant effect on job performance. Third, the compensation has a significant effect on job performance. Fourth, conflict of work life  has a significant effect on job performance. Keywords: Leadership, work condition, compensation, work life conflict, and job performance.